The Effect of Shading Conditions and Mowing Frequency on Plant Diversity, Productivity, Soil Nitrogen and Mineral, and Mineral Profiles of Dominant Forages of Grazing Pasture - Visrialty, Isnatul; Ananta, Dwi; Suyitman, Suyitman; Khalil, Khalil (Universitas Bengkulu, 2025)
The research aimed to study the effect of three different paddock management systems on nitrogen and mineral status of soil, plant diversity, and biomass production and to discuss the potential nutritional effects of macro mineral profiles of dominant forages on grazing cattle. The research was conducted in a Completely Randomized Design (CRD) 3x4, consisting of 3 paddocks as treatments and four plots as replicates. The pasture was divided into three paddocks based on shading conditions and mowing frequency: P1: unshaded by trees and rarely mowed; P2: unshaded but regularly mowed; and P3: shaded by numerous trees and never mowed. Each paddock was divided into four plots based on plant density, with plant and soil samples collected at 17 sampling points per plot. Measured parameters included botanical composition, dominant species, dry matter, and macro mineral concentration of calcium, sodium, phosphorus, sulfur, magnesium, and potassium in the soils and dominant forages. The grazing pasture was inhabited by around 110 native plant species, dominated by Imperata cylindrica (19.6%), Axonopus compressus (16.8%), Mimosa pudica (12.1%), Digitaria sanguinalis (10%), Elephantopus mollis (9.0%), and Euphorbia hirta (8.5%). Biomass production ranged from 110–135 kg/ha/day, with a carrying capacity of 2.5–3.0 AU/ha (significant at p<0.05). Different mowing frequency and shading conditions influenced soil nutrient concentrations, forage diversity, and productivity. Considering requirements for growing cattle, the dominant species had a favorable content in Mg, K, and S but was deficient in P, Na, and Ca. In conclusion, the grazing pasture was populated by diverse native forage plants, and the dominant species were poor in several essential minerals of P, Na, and Ca, which are most likely to limit cattle productivity.